Effects of Academic Degree and Discipline on Religious and Evolutionary Views in Chile and Colombia - Marín, César (Zygon, 2021)
Relationships between degree/area of academic formation and religious and Darwinian views are controversial. This study aimed to compare the religious beliefs and acceptance of Darwinian evolution between two contrasting South American scientific communities (Chile and Colombia), accounting for different degrees and areas of academic formation. In 2018, 115 last year bachelor students (surveyed as freshmen in 2014 for a previous study) from Chile, and 283 first/last year bachelor students, graduate students, and professors from Colombia, all belonging to biology, chemistry, or physics, were surveyed. Chilean students/faculty were significantly more agnostic/atheist, more accepting of Darwinian evolution, and less creationist than their Colombian counterparts. Academic degree and area differently affected these views in both countries, as only in Chile there was a clear tendency among biologists and physicists with higher degrees to hold less religious and creationist views. Marked differences between the history, socioeconomic contexts, and especially in high school and university curricula of both countries might explain these results.